Rho GTPase signaling and role of the Rac1 exchange factor DOCK4 in GBM invasion and vascular growth. (31st January 2018) - Egnuni, Teklu; Speirs, Valerie; Chakrabarty, Aruna; Wurdak, Heiko; Short, Susan; Mavria, Georgia
Abstract: INTRODUCTION: The aggressive nature of brain tumours and resistance to therapy is highly influenced by the tumour microenvironment. A key feature of glioblastoma, also used in diagnosis, is the high degree of aberrant vascularity. Rho GTPases are key regulators of blood vessel growth and morphology. Activation of Rho proteins is controlled by guanine nucleotide exchange factors (GEFs), and GTPase activating proteins (GAPs). The study is focused on understanding the role of the Rac1 GEF DOCK4 in the tumour cell, and stroma cell compartments of glioblastoma. METHODS: i) The role of DOCK4 in invasion was analysed using organotypic spheroid assays ii) DOCK4 expression was determined in patient samples and related to expression of stem cell markers iii) The role of vascular Dock4 was investigated in experimental tumours implanted intracranially in heterozygous Dock4 null mice and treated with radiotherapy. RESULTS: i) DOCK4 knockdown reduced outgrowth of patient derived glioblastoma cells in spheroid assays. ii) Oncomine microarray data showed significant increase of DOCK4 levels in cultured GBM cells isolated from tumours compared to neural stem cells. Immunohistochemical analysis showed correlation between DOCK4 and nestin expression. iii) Analysis of primary and recurrent GBM samples showed larger diameter and blood vessels with more of glomeruloid structures in recurrent tumours iv) Heterozygous Dock4 genetic deletion resulted in reduction of blood vessel diameter. There was reduced tumour burden in response to radiotherapy with Dock4 deletion in the vascular compartment, compared to radiation therapy alone. CONCLUSIONS: Invasion of tumour cells into normal brain parenchyma, and microvascular proliferation of endothelial cells, both pathologic hallmarks of GBM, may be potentially blocked by inhibition of Rac1 signaling and the Rac1 GEF factor DOCK4.